Evaluation of Finger Prints in Relation to Academic Performance of Students in Anatomy at Islam Medical and Dental College, Sialkot - Muhammad Junaid; Riaz Ahmad; Naureen Waseem; Aftab Ahmad; Aaqiba Rasheed; Rana Muhammad Zeeshan; Ayesha Riaz (Journal of Aziz Fatimah Medical and Dental College)
Objective: To assess the relationship between the fingerprint patterns and academic performance of students in Anatomy. Methodology: This Cross-sectional study was conducted in the Anatomy department of Islam Medical and Dental College Sialkot. The duration of the study was from mid-November 2022 to mid-December 2022. A total of 300 healthy medical (1st and 2nd year MBBS) and dental (1st year BDS) students with no injury and deformity, voluntarily participated in this study. The student’s age were 20-22 years. Simple convenient sampling was used. Ethical clearance was obtained before study. Thumb prints were collected along with questionnaire. The study was done by categorizing the pattern into arches, loops and whorls. The academic performance was taken in percentage and classified as above 70 %, between 50 % and 70 % and below 50%. The statistical analysis of categorical data was done by using non-parametric test i.e. chi square test. A P value of < 0.05 was considered statistically significant. Results: The most common pattern observed among students was loops. The students with loop pattern were in high scoring group while students with whorl and arch pattern scored less marks in Anatomy. Conclusion: The percentage of academic performance was higher in students with loops as compared to whorl and arch.